Revolving traditional EEG device into mobile architecture - Muhd Adnan, Hafizuddin; Yaacob, Hamwira Sakti; Abdul Rahman, Abdul Wahab; Othman, Marini (The Institute of Electrical and Electronics Engineers, Inc., 2016)
This Electroencephalogram (EEG) has been widely used to capture brain signals for affective recognition through computational modelling of affective states based on valence, arousal and dominance. Not until recently wireless EEG machines are introduced to record brain signals during physical activities and high range of mobility. Nevertheless, such devices are expensive. Therefore, the aim of this study is to design a mobile EEG systems using an existing stationary EEG amplifier, EXG Brainmarker. The main component for the proposed mobile EEG system are the electrodes cap connected to EXG Brainmarker which will be powered up using portable rechargeable battery, Surface tablet to record and store EEG signals, Portable Wi-Fi device as a medium for remotely connection to monitor the Surface tablet. The proposed EEG mobile system was tested in a Simulation Centre at Akademi Laut Malaysia (ALAM). The data was obtained from three marine pilot who were given tasks to navigate ships in the simulated scenes. Findings and observations from the experiment are reported in this paper. It was also observed that there are several common movements took place when maneuvering the ship such as lift up their hand, turn their head to left and right and a few steps walking.